GC/MS Evaluation and In Vitro Antioxidant Activity of Essential Oil and Solvent Extracts of an Endemic Plant Used as Folk Remedy in Turkey: Phlomis bourgaei Boiss. (13th May 2013) - Sarikurkcu, Cengiz; Sabih Ozer, M.; Cakir, Ahmet; Eskici, Mustafa; Mete, Ebru
Abstract : This study was outlined to examine the chemical composition of hydrodistilled essential oil and in vitro antioxidant potentials of the essential oil and different solvent extracts of endemic Phlomis bourgaei Boiss. used as folk remedy in Turkey. The chemical composition of the oil was analyzed by GC and GC-MS, and the predominant components in the oil were found to be β -caryophyllene (37.37%), (Z) - β -farnesene (15.88%), and germacrene D (10.97%). Antioxidant potentials of the solvent extracts and the oil were determined by four testing systems including β -carotene/linoleic acid, DPPH, reducing power, and chelating effect. In β -carotene/linoleic acid assay, all extracts showed the inhibition of more than 50% at all concentrations. In DPPH, chelating effect, and reducing power test systems, the water extract with 88.68%, 77.45%, and 1.857 (absorbance at 700 nm), respectively, exhibited more excellent activity potential than other extracts (hexane, ethyl acetate and methanol) and the essential oil at 1.0 mg/mL concentration. The amount of the total phenolics and flavonoids was the highest in this extract (139.50 ± 3.98  μ g gallic acid equivalents (GAEs)/mg extract and 22.71 ± 0.05 μ g quercetin equivalents (QEs)/mg extract).